Signal Transduction: Pathways, Mechanisms and Diseases - Sitaramayya, Ari (Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book was adapted from graduate courses on signal transduction taught by the editor, where the need for a good overview of recent developments on each of the topics being discussed became apparent. Given the wide range of research topics in signaling, a selection was made that not only reflects the current research interest, but also anticipates those areas that will continue to be of interest over the next several years. The health-relatedness of research was a major criterion for selection, as can be seen in the list of topics covered, such as G protein coupled receptors, growth factors, nuclear receptors, reactive oxygen and nitrogen species, the cell cycle and cancer. The emphasis is on areas of signaling research with direct clinical significance. Another field covered, one rarely highlighted in signal transduction books, is that of signaling platforms, which has been emerging as a significant research area relevant to cellular metabolism, cell proliferation, differentiation, apoptosis, neurodegenerative diseases, and cancer.